Updated German guideline on diagnosis and treatment of squamous cell carcinoma and adenocarcinoma of the esophagus - Porschen, Rainer; Fischbach, Wolfgang; Gockel, Ines; Hollerbach, Stephan; Hölscher, Arnulf; Jansen, Petra Lynen; Miehlke, Stephan; Pech, Oliver; Stahl, Michael; Vanhoefer, Udo; Ebert, Matthias (United european gastroenterology journal, 2024)
Diagnosis and therapy of esophageal carcinoma is challenging and requires a multidisciplinary approach. The purpose of the updated German guideline “Diagnosis and Treatment of Squamous Cell Carcinoma and Adenocarcinoma of the Esophagus—version 3.1” is to provide practical and evidence-based advice for the management of patients with esophageal cancer. Recommendations were developed by a multidisciplinary expert panel based on an extensive and systematic evaluation of the published medical literature and the application of well-established methodologies (e.g. Oxford evidence grading scheme, grading of recommendations). Accurate diagnostic evaluation of the primary tumor as well as lymph node and distant metastases is required in order to guide patients to a stage-appropriate therapy after the initial diagnosis of esophageal cancer. In high-grade intraepithelial neoplasia or mucosal carcinoma endoscopic resection shall be performed. Whether endoscopic resection is the definitive therapeutic measure depends on the histopathological evaluation of the resection specimen. Esophagectomy should be performed minimally invasive or in combination with open procedures (hybrid technique). Because the prognosis in locally advanced esophageal carcinoma is poor with surgery alone, multimodality therapy is recommended. In locally advanced adenocarcinomas of the esophagus or esophagogastric junction, perioperative chemotherapy or preoperative radiochemotherapy should be administered. In locally advanced squamous cell carcinomas of the esophagus, preoperative radiochemotherapy followed by complete resection or definitive radiochemotherapy without surgery should be performed. In the case of residual tumor in the resection specimen after neoadjuvant radiochemotherapy and R0 resection of squamous cell carcinoma or adenocarcinoma, adjuvant immunotherapy with nivolumab should be given. Systemic palliative treatment options (chemotherapy, chemotherapy plus immunotherapy, immunotherapy alone) in unresectable or metastastic esophageal cancer depend on histology and are stratified according to PD-L1 and/or Her2 expression.
Erstmals veröffentlicht: 29. Januar 2024
Gesehen am 03.02.2025